2023
DOI: 10.1007/s40843-022-2414-2
|View full text |Cite
|
Sign up to set email alerts
|

Atomically dispersed platinum supported onto nanoneedle-shaped protonated polyaniline for efficient hydrogen production in acidic water electrolysis

Abstract: Developing high-performance single-atom platinum (Pt) catalysts for acidic hydrogen evolution reaction (HER) is of significance. However, their HER kinetics are limited due to the low concentration of hydrogen ions (H + ) near the Pt sites in acidic electrolytes, where hydronium ions are undesirably formed with H + surrounded by water molecules. Here, we seek to improve the HER kinetics by anchoring single-atom Pt catalyst on nanoneedle-shaped protonated polyaniline supports, which can not only capture H + fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Recently, fundamental changes in the electronic and catalytic properties of the metal have been reported as precious metal or transition metal catalysts decrease from volume to nanoparticle to single atomic size. Owing to the single metal active centers, the single atom catalysts (SACs) have been used for various energy conversion catalytic reactions due to their high activity and selectivity toward specific products [39][40][41]. Owing to the isolated single atoms as catalytic centers, the SACs can potentially suppress the N-N coupling and inhibit the introduction of double-nitrogen by-product, thus promoting the selectivity of NH 3 synthesis [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fundamental changes in the electronic and catalytic properties of the metal have been reported as precious metal or transition metal catalysts decrease from volume to nanoparticle to single atomic size. Owing to the single metal active centers, the single atom catalysts (SACs) have been used for various energy conversion catalytic reactions due to their high activity and selectivity toward specific products [39][40][41]. Owing to the isolated single atoms as catalytic centers, the SACs can potentially suppress the N-N coupling and inhibit the introduction of double-nitrogen by-product, thus promoting the selectivity of NH 3 synthesis [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen energy, a good prospect as an alternative to fossil fuels, is extensively used in energy conversion, chemical industry, and other fields. 1,2 Water electrolysis can utilize the electrical energy to convert H 2 O into H 2 and O 2 , which is considered one of the most arousing systems for efficient hydrogen production. 3,4 Oxygen evolution reaction (OER) is essential for the efficient water electrolysis to produce hydrogen, which necessitates a four-electron proton transfer with complicated intermediates and sluggish kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical water splitting has become an inspiring route for efficient hydrogen production using renewable clean energy. 1–3 The oxygen evolution reaction (OER), the anodic reaction of water splitting, remains a bottleneck limiting the energy efficiency, which renders slower reaction kinetics compared to the cathodic reaction of water splitting. Numerous previous studies have revealed that an iridium (Ir)-based catalyst is one of the most appropriate OER catalysts, due to the appropriate adsorption energies for reaction intermediates.…”
mentioning
confidence: 99%